PENINGKATAN PROSES PEMBELAJARAN TEMATIK DENGAN MODEL ACCELERATED LEARNING DI KELAS III SD NEGERI 18 SINAPA PILIANG KEC. LUBUK SIKARAH KOTA SOLOK - Riri Kartika (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2016)
ABSTRACT This research was aimed at improving the students’ thematic learning by using accelerated learning model in class III of SDN 18 Sinapa Piliang Kota Solok. The result of the research indicated that, In the first cycle, the average score of the students on the six lessons was 73.88 for which they were in adequate category (the average score was between (65-80%), this then improved into 79,35 in the second cycle for which they were in adequate category (the average score was between 65-80%). In the third cycle, their average score improved into 83 for which they were in good category (the average score was between 80-100%). The learning process conducted by the teacher improved from 72,1 in the first cycle into 80,55 in the second cycle, and it became 90,5 in the third cycle. Meanwhile, the students’ aspect improved from 73 in the first cycle into 78 in the second cycle, and it became 89 in the third cycle. Based on these result, it was concluded that the thematic learning could be improved by using accelerated learning model. Keywords : Accelerated learning, Learning model,  Thematic learning